Circadian Kisspeptin expression in human term placenta. Issue 11 (November 2015) - de Pedro, M.A.; Morán, J.; Díaz, I.; Murias, L.; Fernández- Plaza, C.; González, C.; Díaz, E.
Abstract: Kisspeptin is an essential gatekeeper of reproductive function. During pregnancy high circulating levels of kisspeptin have been described, however the clear role of this neuropeptide in pregnancy remains unknown. We tested the existence of rhythmic kisspeptin expression in human full-term placenta from healthy pregnant women at six different time points during the day. The data obtained by Western blotting were fitted to a mathematical model (Fourier series), demonstrating, for the first time, the existence of a circadian rhythm in placental kisspeptin expression. Highlights: Kisspeptins are expressed in human full term placenta in a circadian manner. Highest kisspeptin values appear at 04:00 h. Placental kisspeptin rhythm matched with the well-known melatonin rhythm.